MMP-3 Contributes to Nigrostriatal Dopaminergic Neuronal Loss, BBB Damage, and Neuroinflammation in an MPTP Mouse Model of Parkinson's Disease - Young Cheul Chung; Yoon-Seong Kim; Eugene Bok; Tae Young Yune; Sungho Maeng; Byung Kwan Jin (Hindawi Limited, 2013)
The present study examined whether matrix metalloproteinase-3 (MMP-3) participates in the loss of dopaminergic (DA) neurons in the nigrostriatal pathway in a 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) mouse model of Parkinson's disease with blood brain barrier (BBB) damage and infiltration of peripheral immune cells. Tyrosine hydroxylase (TH) immunostaining of brain sections from MPTP-treated mice showed that MPTP induced significant degeneration of nigrostriatal DA neurons. Moreover, FITC-labeled albumin detection and immunostaining revealed that MPTP caused damage to the BBB and increased the number of ED-1- and CD-3-immunopositive cells in the substantia nigra (SN). Genetic ablation of MMP-3 reduced the nigrostriatal DA neuron loss and improved motor function. This neuroprotective effect afforded by MMP-3 deletion was associated with the suppression of BBB disruption and a decrease in the number of ED-1- and CD-3-immunopositive cells in the SN. These data suggest that MMP-3 could play a crucial role in neurodegenerative diseases such as PD in which BBB damage and neuroinflammation are implicated.